Distribution of the common hamster in the Czech Republic after 2000: retreating to optimum lowland habitats - Tkadlec, Emil; Heroldová, Marta; Víšková, Veronika; Bednář, Marek; Zejda, Jan
Abundances of the common hamster in western Europe declined dramatically over the last 30 years. Recently, severe restrictions in distribution range have also been reported from central European countries. Here we update knowledge of the hamster distribution range in the Czech Republic based on information from six independent sources: (1) monitoring programme for the common vole carried out by State Phytosanitary Administration, (2) monitoring carried out directly by us, (3) questionnaire data from farming companies, (4) questionnaire data from district museums, (5) data from a public server BioLib for mapping species distribution, and (6) observations from nonrelated research activities and persons taking interest in hamsters. The comparison of locations detected after 2000 with those from the last survey > 30 years ago suggests that the range is severely reduced with hamsters retreating to the optimum lowland habitats along large rivers. These results suggest that the demographic mechanisms causing population decline in western populations operate in central Europe as well.